Effect of a diet intervention on cardiometabolic outcomes: Does race matter? A randomized clinical trial. (February 2021) - Kahleova, Hana; Rembert, Emilie; Nowak, Amber; Holubkov, Richard; Barnard, Neal D.
Summary: Background & aims: In the U.S., Blacks as a group have an earlier onset, greater severity, and earlier mortality from cardiovascular disease than their White peers. The aim of this study was to test whether Black and White individuals experience similar cardiovascular risk reduction in response to a dietary intervention. Methods: In the course of a randomized trial assessing the effect of low-fat plant-based dietary intervention on cardiometabolic outcomes in overweight adults, this study compared the effects of a 16-week intervention in Black and White participants. Results: We randomly assigned 244 participants to the intervention (n = 122, including 60 Blacks and 57 Whites) or control (n = 122, including 53 Blacks and 60 Whites) groups. The full study was completed by 222 (91.0%) participants. There were no significant differences between Blacks and Whites in changes in body mass index (−2.3 kg/m2 in both races; p-value for the difference between Blacks and Whites p = 0.99), insulin resistance (Blacks −1.9, Whites −0.85; p = 0.30), total cholesterol (Blacks −0.73 mmol/L, Whites −0.69 mmol/L p = 0.89), LDL-cholesterol (Blacks −0.59 mmol/L, Whites −0.68 mmol/L p = 0.76), or any other measure. Conclusions: Our data suggest that a healthful plant-based diet improves measures of cardiometabolic health independent of race. Trial registration: ClinicalTrials.gov number, NCT02939638.